Investigating rural library usage among rural youth in Malaysia: its corresponding determinants and impacts - Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva (Canadian Center of Science and Education, 2012)
The demands for information are increasing nowadays, providing adequate sources of information for the community is a crucial agenda as it is an essential part of community development particularly the youth; the future leader of our community. As information and communication technology (ICT) play significant roles as sources of information, similarly, the rural library in Malaysia can play the same roles in offering updated and needed information of the community. The main objective of this paper is to know the potential factors, benefits and problems in using the services provided in the rural library. Discussion of this paper is based on applied documents and literature analysis. Based on the analyses done, a number of potential benefits offered by the rural community have been identified and certainly information offered is the main benefit available. Potential problems faced by the rural community in using the rural library services need to be overcome to ensure the rural community will profits from the benefits offered. Besides, a number of related factors and theories have been further discussed.